Features of structural and geometric remodeling of the heart and changes in the diastolic filling of the heart in patients with chronic heart failure of ischemic genesis with preserved left ventricular ejection fraction - V. A. Lysenko; M. S. Potapenko; V. V. Syvolap (Zaporozhye State Medical University, 2021)
Chronic heart failure (CHF) is the most common cardiovascular disease worldwide, estimated at 23 million. With the increase in the growing of the elderly population, the prevalence of hypertension, atrial fibrillation, obesity, diabetes, as well as the improvement of ultrasound diagnostic methods, a further increase in the number of cases of CHF with preserved left ventricular EF. Despite the large number of studies dedicated to analyzing the features of structural and geometric remodeling of the heart, changes in the systolic and diastolic function of the ventricles in patients with CHF, this issue hasn't been definitively resolved and needs further improvement. The aim of the work - to investigate changes in structural and geometric parameters and diastolic function of the heart in patients with CHF of ischemic origin with preserved LV EF. Materials and methods. The study was included 43 patients (men - n = 19; women - n = 24) for CHF of ischemic origin with preserved LV EF, with sinus rhythm, stage II AB, II-IV FC for NYHA (main group), and 90 patients on coronary heart disease without signs of CHF (men - n = 40 (44.5 %); women - n = 50 (55.5 %)), (comparison group). Groups of patients were comparable in age, sex, height, weight, body surface area. Doppler echocardiographic examination was performed on the device Esaote MyLab Eight (Italy). Results. In patients with CHF preserved LV EF, the indicators prevailed: the size of the LA by 25 % (P = 0.005), the long axis of the LA by 11 % (P = 0.001), the LV EDV index of the LV by 13 % (P = 0.042), the LV mass index by 16 % (P = 0.013) according to the Penn Convention and (P = 0.004) the ASE. Eccentric left ventricular hypertrophy was diagnosed in 56 % of patients. Diastolic left ventricular dysfunction was absent in 2 % of patients with CHF. In 72 % of cases, the type of "relaxation disorder" was established, and in 26 % - "pseudonormal" LV filling profile. In none of the cases was a "restrictive" LV filling profile recorded. The following indicators of left ventricular diastolic function were lower in patients with CHF: e' of the medial fibrous ring of the mitral valve by 26 % (P = 0.0001) and e' lateral by 21 % (P = 0.0001), and the A' the medial fibrous ring of mitral valve by 9 % (P = 0.022), and greater ratios of velocities E/e' medial by 41 % (P = 0.0001), and E/e' lateral fibrous ring of the mitral valve by 28 % (P = 0.0001), mean E/e' by 36 % (P = 0.0001), which indicates a significant increase in end-diastolic pressure in the left ventricle. Conclusions. Structural and geometric remodeling of the heart in patients with CHF with preserved LV EF was characterized by dilatation of the left atrium, a moderate increase in the LV EDV index by 13 % (P = 0.042), a 16 % increase (P = 0.013) in the LV mass index, with the formation eccentric (56 %) and concentric (18 %) LV hypertrophy. Diastolic left ventricular dysfunction was absent in 2 % of patients with CHF. Disorders of diastolic filling of the left ventricle (72 % "relaxation disorder" and 26 % "pseudonormal" type) were occurred due to an increase in end-diastolic pressure in the left ventricle (increase by 41 % (P = 0.0001) ratio E/e' medial fibrous ring MK), in LA (increase of more than 2 times (P = 0.0001) pulmonary capillary wedge pressure), and was accompanied by the development of postcapillary pulmonary hypertension (increase by 34 % (P = 0.0001) systolic pressure in the pulmonary artery). Despite the preserved LV EF, patients with CHF had significantly lower left and right ventricular contractility (10 % MAPSE med (P = 0.031), 18 % S med (P = 0.001) and 19 % (P = 0.007) RV EF).